To the 100th anniversary of the library of South Ukrainian National Pedagogical University named after K. D. Ushynsky: history and the present - Spasskova Olena; Goncharenko Natalia (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2022)
In 2022, the library of South Ukrainian National Pedagogical University named after K. D. Ushynsky celebrates its 100th anniversary, which makes us return to the origins of higher pedagogical education in the South of the country. It is this fact that determines the relevance of our research. The article traces the history of the university and the library, starting from the 20s of the 20th century to the present day. The purpose of the article consists in the necessity to analyse the history of the creation and development of the university and the library in inseparable interaction. The historical method of research allowed us to systematise and summarise the available information on the history of the library of Ushynsky University in chronological order. The article examines the main stages of the existence of Ushynsky University, starting from its foundation in 1920, when it received the name of the Institute of National Education and the task of providing training for education workers in the South of Ukraine. It was also found that the library of this educational institution was created in 1922 to provide students with textbooks and fiction. It is shown how our higher educational institution survived the educational reforms implemented by the new, at that time, Soviet government. On the basis of archival documents and memories of employees stored in the library, the history of the evacuation of the university and the library during the Second World War alongside their post-war revival has been traced. The problems of the development of the university, the introduction of new educational directions, the opening of new faculties and the process of rebuilding the library in the second half of the 20th and the beginning of the 21st centuries have been revealed. Considerable attention is devoted to the current state of the library, its structure, aspects of activity and challenges. It was concluded that the library of Ushynsky University is an important structural unit that contributes to the teaching / learning activities, research-oriented, cultural and education-related activities of teachers and students. It has been proved that today the library is a powerful information institution, a scientific and cultural centre of the university.